Ignoring Emerging Infectious Diseases: The Fatal Error That Could Lead to the Next Pandemic - Vidovic, Karlo (Trinity Student Medical Journal, 2024)
Emerging Infectious Diseases (EIDs) are a group of novel or re-surging infectious pathogens which primarily originate from animal populations. Many EIDs have a pandemic-causing ability and should be a top priority for governments worldwide. The primary strategies that should be implemented to prevent a pandemic caused by emerging pathogens revolve around preventing the transfer of zoonoses via diligent surveillance methods involving classical tools, data science, and artificial intelligence. The equitable use of mRNA vaccine templates can decrease the spread, morbidity, and mortality of viral and possibly other pathogenic EIDs. Governments must invest in creating stable healthcare systems and well-equipped research facilities to handle the burden of EID outbreaks.